2023
DOI: 10.3389/fenvs.2023.1137835
|View full text |Cite
|
Sign up to set email alerts
|

Employing the agricultural classification and estimation service (ACES) for mapping smallholder rice farms in Bhutan

Abstract: Creating annual crop type maps for enabling improved food security decision making has remained a challenge in Bhutan. This is in part due to the level of effort required for data collection, technical model development, and reliability of an on-the-ground application. Through focusing on advancing Science, Technology, Engineering, and Mathematics (STEM) in Bhutan, an effort to co-develop a geospatial application known as the Agricultural Classification and Estimation Service (ACES) was created. This paper foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 79 publications
0
0
0
Order By: Relevance
“…These methods are useful for analyzing the relationship between target variables and multiple input features and are more efficient and accurate than single-learner models [15][16][17]. Ndikumana et al [18] using satellite data to estimate rice biomass, found that RFR produced better performance compared to other ML algorithms tested (e.g., Support Vector Regression). Zhang et al [19] used UAV imagery to study multiple traits in rice at two fertility stages, finding that the RFR algorithm outperformed SVR and ANN.…”
Section: Introductionmentioning
confidence: 99%
“…These methods are useful for analyzing the relationship between target variables and multiple input features and are more efficient and accurate than single-learner models [15][16][17]. Ndikumana et al [18] using satellite data to estimate rice biomass, found that RFR produced better performance compared to other ML algorithms tested (e.g., Support Vector Regression). Zhang et al [19] used UAV imagery to study multiple traits in rice at two fertility stages, finding that the RFR algorithm outperformed SVR and ANN.…”
Section: Introductionmentioning
confidence: 99%